AWARENESS, KNOWLEDGE, AND ATTITUDE TOWARDS VIRTUAL AND AUGMENTED REALITY TECHNOLOGIES IN PHYSIOTHERAPY PRACTICE AMONG FINAL YEAR PHYSIOTHERAPY STUDENT AT A SUBSAHARAN AFRICAN UNIVERSITY (Journal of Biomedical Investigation, 2025)
Background: Technological innovations such as virtual reality (VR) and augmented reality (AR) are transforming healthcare education and clinical practice. These immersive technologies offer opportunities for interactive, experiential learning and can enhance rehabilitation outcomes. However, the extent to which physiotherapy students are aware of, knowledgeable about, and have a positive attitude toward VR/AR remains underexplored, especially in resource-limited settings like Nigeria.Aim: To assess the awareness, knowledge, and attitudes of final-year physiotherapy students toward the application of VR and AR in physiotherapy practice across selected Nigerian institutions. Materials and methods: A descriptive cross-sectional study was conducted among 400 final-year physiotherapy students from five Nigerian universities using a self-structured, validated online questionnaire. The tool assessed participants' demographic details, familiarity with VR/AR, practical knowledge, and attitudes. Data was summarized using descriptive statistics and visual representations.Results: While 74.2% of students were aware of VR/AR applications in physiotherapy, only 1.8% had good knowledge, and just 1.0% had practical experience using VR/AR. However, 62.4% strongly agreed that VR/AR should be integrated into physiotherapy practice, and 58.8% expressed high interest in learning more. Major barriers identified included lack of exposure in the curriculum, insufficient equipment, and inadequate instructor training.Conclusion: Although final-year physiotherapy students in Nigeria showed high awareness and interest in VR/AR, practical knowledge and experience remain low. The findings support the urgent need to integrate VR/AR into physiotherapy curricula through hands-on training, workshops, and institutional investment to prepare future practitioners for technology-enhanced rehabilitation.
Keywords: Virtual reality; Augmented reality; Physiotherapy students; Rehabilitation; Nigeria; Health Technology Education